2022
DOI: 10.1017/ash.2022.313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors associated with outpatient parenteral antimicrobial therapy (OPAT) complications: A retrospective cohort study

Abstract: Objective: To characterize factors associated with increased risk of outpatient parenteral antimicrobial therapy (OPAT) complication. Design: Retrospective cohort study. Setting: Four hospitals within NYU Langone Health (NYULH). Patients: All patients aged ≥18 years with OPAT episodes who were admitted to an acute-care facility at NYULH between January 1, 2017, and December 31, 2020, who had an infectious diseases consultation during admission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…In a large US cohort of OPAT patients, racial disparities in safety outcomes were measured but not observed. 26 In a separate, smaller cohort of US-based patients receiving treatment for prosthetic joint infection, non-White race was associated with PICC-related ED visits. 27 Prior investigations evaluating care transitions beyond those specific to OPAT have demonstrated racial disparities in scheduled and unscheduled care following discharge from acute care.…”
Section: Resultsmentioning
confidence: 96%
“…In a large US cohort of OPAT patients, racial disparities in safety outcomes were measured but not observed. 26 In a separate, smaller cohort of US-based patients receiving treatment for prosthetic joint infection, non-White race was associated with PICC-related ED visits. 27 Prior investigations evaluating care transitions beyond those specific to OPAT have demonstrated racial disparities in scheduled and unscheduled care following discharge from acute care.…”
Section: Resultsmentioning
confidence: 96%
“…Krah et al evaluated the economic burden of OPAT versus oral therapy and showed that the average daily cost for OPAT group was $65 (CI 51 to 78 compared to $7 (CI, 4–9) for the oral therapy group, demonstrating more than 9-fold higher costs with OPAT [26]. This does not include CVL complications such as line dislodgement, leak, bleeding, occlusion, thrombosis, and CVL-related BSI, with rates as high as 8.45% [27 ▪ ]. With the growing body of evidence to suggest noninferiority of oral therapy to IV therapy, early transition to oral antibiotic therapy may be more cost-effective [28 ▪▪ ].…”
Section: Early Switch From Intravenous To Oral Therapymentioning
confidence: 99%
“…Multiple studies have outlined worse outcomes or increased risk of complications or readmission in patients lost to ID follow-up. 1,2 Although these researchers hypothesized that communication challenges and possible staffing issues were contributory to loss to follow-up, external validity of the findings could be improved if further characteristics of the acute rehabilitation center, subacute rehabilitation center, and LTCF were shared and existing methods of communication with these facilities described. Herein, we describe our institutional experience with off-site facilities.…”
mentioning
confidence: 99%